Assessment of Cognitive Function with Sleep Spindle Characteristics in Adults with Epilepsy. (17th April 2023) - Huang, Yajin; Liu, Yaqing; Song, Wenjun; Liu, Yanjun; Wang, Xiaoqian; Han, Juping; Ye, Jiang; Han, Hongmei; Wang, Li; Li, Juan; Wang, Tiancheng
Abstract : Objective . Epilepsy may cause chronic cognitive impairment by disturbing sleep plasticity. Sleep spindles play a crucial role in sleep maintenance and brain plasticity. This study explored the relationship between cognition and spindle characteristics in adult epilepsy. Methods . Participants underwent one-night sleep electroencephalogram recording and neuropsychological tests on the same day. Spindle characteristics during N2 sleep were extracted using a learning-based system for sleep staging and an automated spindle detection algorithm. We investigated the difference between cognitive subgroups in spindle characteristics. Multiple linear regressions were applied to analyze associations between cognition and spindle characteristics. Results . Compared with no/mild cognitive impairment, epilepsy patients who developed severe cognitive impairment had lower sleep spindle density, the differences mainly distributed in central, occipital, parietal, middle temporal, and posterior temporal (P < 0.05 ), and had relatively long spindle duration in occipital and posterior temporal P < 0.05 . Mini-Mental State Examination (MMSE) was associated with spindle density (pars triangularis of the inferior frontal gyrus (IFGtri): β = 0.253, P = 0.015, and P . adjust = 0.074 ) and spindle duration (IFGtri: β = − 0.262, P = 0.004, and P . adjust = 0.030 ). Montreal Cognitive Assessment (MoCA) was associated with spindle duration (IFGtri: β = − 0.246, P = 0.010, and P . adjust = 0.055 ). Executive Index Score (MoCA-EIS) was associated with spindle density (IFGtri: β = 0.238, P = 0.019, and P . adjust = 0.087 ; parietal: β = 0.227, P = 0.017, and P . adjust = 0.082 ) and spindle duration (parietal: β = − 0.230, P = 0.013, and P . adjust = 0.065 ). Attention Index Score (MoCA-AIS) was associated with spindle duration (IFGtri: β = − 0.233, P = 0.017, and P . adjust = 0.081 ). Conclusions . The findings suggested that the altered spindle activity in epilepsy with severe cognitive impairment, the associations between the global cognitive status of adult epilepsy and spindle characteristics, and specific cognitive domains may relate to spindle characteristics in particular brain regions.